Association Between Intrapartum Magnesium Administration and the Incidence of Maternal Fever: A Retrospective Cross-sectional Study. Issue 3 (September 2018) - Lange, E.M.S.; Segal, S.; Pancaro, C.; Wong, C.A.; Grobman, W.A.; Russell, G.B.; Toledo, P.
Abstract : ( Anesthesiology . 2017;127:942–952) Maternal fever is associated with neonatal seizures, cerebral palsy, hypotonia, and other adverse neonatal outcomes; it complicates up to one third of all labors. Increased levels of interleukin 6 (IL-6) have been observed in maternal fever, in both inflammatory and infectious etiologies. In animals, magnesium sulfate has suppressed IL-6 induced maternal fevers and is used in humans to reduce the risk of cerebral palsy in infants. This study aimed to investigate the association between intrapartum maternal fever and maternal magnesium administration.